### Home > GB8I > Chapter cc46 > Lesson cc46.2.2 > Problem 6-64

6-64.

Kevin and his little sister, Katy, are trying to solve the system of equations shown below. Kevin thinks that using the Substitution Method should give a new equation of 3(6*x*– 1) + 2*y*= 43, while Katy thinks it should be 3*x*+ 2(6*x*− 1) = 43. Who is correct and why? Homework Help ✎*y*= 6*x*− 1

3*x*+ 2*y*= 43

In order to solve the system of equations 6*x* - 1 must be substituted in for *y*.

3*x* + 2( 6*x* - 1 ) = 43

Katy is right.